Stealthy microbes: How Neisseria gonorrhoeae hijacks bulwarked iron during infection - Stoudenmire, Julie Lynn; Greenawalt, Ashley Nicole; Cornelissen, Cynthia Nau (Frontiers in Cellular and Infection Microbiology, 2022)
Transition metals are essential for metalloprotein function among all domains of life. Humans utilize nutritional immunity to limit bacterial infections, employing metalloproteins such as hemoglobin, transferrin, and lactoferrin across a variety of physiological niches to sequester iron from invading bacteria. Consequently, some bacteria have evolved mechanisms to pirate the sequestered metals and thrive in these metal-restricted environments. Neisseria gonorrhoeae, the causative agent of the sexually transmitted infection gonorrhea, causes devastating disease worldwide and is an example of a bacterium capable of circumventing human nutritional immunity. Via production of specific outer-membrane metallotransporters, N. gonorrhoeae is capable of extracting iron directly from human innate immunity metalloproteins. This review focuses on the function and expression of each metalloprotein at gonococcal infection sites, as well as what is known about how the gonococcus accesses bound iron.